Colchicine, Aspirin, and Montelukast – A Case of Successful Combined Pharmacotherapy for Adult Multisystem Inflammatory Syndrome in COVID-19 - Downing, Sean (J Glob Infect Dis, 2020)
Since the beginning of the COVID-19 pandemic, many therapeutic strategies have been tried, with mixed results, to prevent and treat adult multisystem inflammatory syndrome in COVID-19 (AMIS-COVID-19). The reason behind this may the complex web of highly intertwined pathophysiologic mechanisms involved in the SARS-CoV-2 infection and the corresponding human systemic response, leading to end-organ damage, disability, and death. Colchicine, high-dose aspirin, and montelukast are being investigated currently as potential modulators of AMIS-COVID-19 in patients who fail to improve with traditional therapeutic approaches. Here, we present a patient who presented with high fevers, extreme fatigue and dyspnea, and ongoing deterioration. As part of our clinical approach, we used the simultaneous combination of the three agents listed above, capitalizing on their different respective mechanisms of action against AMIS-COVID-19. Following the initiation of therapy, the patient showed symptomatic improvement within 24 h, with the ability to return to daily activities after 72 h of continued triple-agent approach. Based on this experience, we have reviewed the immunomodulatory basis of this regimen, including potential avenues in which it may prevent the development of cytokine release syndrome (CRS) and its clinical manifestation, AMIS-COVID-19. By blocking the early stages of an inflammatory response, via diverse mechanistic pathways, the regimen in question may prove effective in halting the escalation of CRS and AMIS-COVID-19 in acutely symptomatic, nonimproving COVID-19 patients.